Department of Forensic Medicine & Toxicology, Sardar Patel Medical College, Bikaner (Rajasthan) (Journal of Forensic Medicine & Toxicology, 2023)
Burns are still a substantial health risk in middle- and low-income nations, where preventive measures and burn patient care are only partially implemented. Burns are also a principal cause of morbidity; millions of people who survive are left with permanent disabilities and disfigurements, as well as emotional distress and discrimination. During the study period, 2363 cases were brought in the mortuary for autopsy, out of those there were 153 cases of burn victims giving incidence of 6.47%. All the information regarding deceased and the circumstances of death were collected from the concerned police officer/relatives or from the photograph of the scene of occurrence. A multidisciplinary approach involving a crime scene investigation, an autopsy, and a thorough toxicological analysis is needed for the medico-legal examination of burned dead bodies in order to identify the victim, determine their vitality prior to being exposed to fire, and determine the cause of death. The autopsy surgeon must be well-versed in the socio-demographic and epidemiological aspects that affect the occurrence of burns prior to doing the autopsy in a burn case. In the present study, an effort is made to analyze the data gathered on such cases to determine the demographic profile of deaths due to burn in central India (Indore) region.
Keywords: Burn; Autopsy; Demography